Building Intention to Use in Educational Institution: How Service Quality and Reputation Drive Student Satisfaction - Sabar Arifin; Darjat Sudarjat (Husnayain Business Review, 2026)
This study examines how service quality and institutional reputation shape students’ intention to continue their studies. It also investigates the extent to which satisfaction mediates the formation of students’ intention to use (continue using) study services at the same institution. A quantitative method was employed, involving 178 lower-secondary students as respondents; data were analyzed using SmartPLS. The findings show that perceived institutional reputation influences students’ intention to continue their studies, whereas service quality—despite affecting student satisfaction—does not influence intention to continue. Likewise, satisfaction as a mediator does not affect intention to continue. These results are expected to benefit the education sector—especially educational marketing and service management—in designing strategies to enhance and communicate institutional reputation and to develop more distinctive, impressive student services.